Media Pembelajaran untuk Siswa Sekolah Dasar - Apriyanur Rohim; Indah Setyo Wardhani (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
Instructional media plays a crucial role in improving the quality of education in elementary schools. This article examines the importance of using appropriate instructional media for elementary school students to support a more effective, interactive, and enjoyable learning process. The use of media such as visuals, audio, and multimedia can help students understand abstract and complex concepts, while also boosting their motivation and participation in learning. Instructional media can also accommodate various learning styles, which accelerates understanding and enhances retention of the material. Additionally, this article explores the most effective types of media for use in elementary schools, as well as the challenges that may arise during its implementation in educational settings. Research indicates that integrating the right instructional media can create a more dynamic learning environment and support students' cognitive development. This study was implemented at SDN 1 Kamal Bangkalan. The goal of the research is to make the teaching and learning process more engaging, enhance learning effectiveness, and support diverse learning styles.